Does Alice Live Here Anymore? Autonomy and Identity in Persons Living and Dying With Dementia - D'cruz, Migita M. (Frontiers in Psychiatry, 2021)
Conventional scientific definitions of dementia, or its newer proposed alternate – neurocognitive disorders place emphasis upon cognitive function, particularly memory. The changes in thought, emotion, behaviour, personality and biological function are usually considered only of secondary importance. At the core of the illness, however, lies a progressive loss of self, and by extension, of personhood, identity, autonomy and agency. The identity of the person living with dementia, and the deterioration of a sense of self assumes significance in planning end of life care, including palliative care. A consideration of self and identity is also significant where physician assisted death, incorporating euthanasia, has legal sanctity. As dementia progresses, there is usually a progressive loss of personal decision making capacity and legal competence. Shared decision making, advance care directives and proxy representatives are options available to safeguard autonomy and agency in such cases. Advance care directives are often treated as static documents. The loss of self and deterioration of identity in persons with dementia means, that there is a psychological discontinuity across time and space, though biological continuity is retained. The discontinuity in self and identity however, imply that the person with dementia changes considerably and so too may values and beliefs. A document which best reflected the wishes of the person with dementia in the past, may not always do so now. Advance directives and proxy representatives may need to be dynamic and evolve over time, particularly where end of life care and physician assisted death is being invoked.